Analysis of the Causes of The Professional Driver Shortage: A Case Study in Poland - Joanna SEK; Zuzanna SROCZAK (Communications of International Proceedings, 2024)
Road transport has recently been facing several groups of problems that have a significant impact on the efficiency of transportation within various supply chains. These may include, among others, the relatively frequent changes in legislation and the need for carriers to comply with their provisions, which generates additional business costs. It seems that currently, the most important problem for the road transport industry is the insufficient number of professional drivers. Analysing the available literature on this branch of transportation, there are several publications focusing on the issues. However, aspects related to factors influencing entry into work as a professional driver seem to be overlooked and constitute a research gap. The article presents an analysis of the factors influencing the perception of the driving profession as unattractive from the point of view of potential employees. For the analysis, a questionnaire dedicated to Polish professional drivers was developed and completed by 455 respondents. Analysis of the responses showed that despite the many risks drivers face in their work, most of them would choose this career path again. The article also includes suggestions for systemic solutions, which, although they require legislative changes, but can increase safety in road transport and interest in this profession among potential employees. It is worth recalling that the problems indicated by the respondents relating to the Polish road transport market can also be observed in international transport.
Keywords: road transport; risk factors; drivers; supply chain